Strategies and Feasibility Studies of Cattle Fattening Business - Rizky Andri Ulaan, Aldi; Maya Damayanti, Sylviana (The Indonesian Journal of Business Administration, 2016)
The purpose of this study was to find out the feasibility and the benefit of beef cattle fattening by Fresh Farm, Bandung Regency. As the business will begin to be developed, requiring sizable capital. The capital can be obtained either from banks or investors. Of course, both of which require a study of the feasibility of the business to be developed by the Fresh Farm. In this study the feasibility Fresh Farm analyzed, starting from the outside environment analysis, Porter's five forces and financial feasibility. Financially, the business Fresh Farm is considered feasible, amounting to Rp2,359,552,333 positive NPV, IRR 44.66%, Net B/C 2.19, Payback Period 1.8, and ROI 50%. Implementation of business with the application of the principles of good management, it is proposed in the research results.Â Keywords: crowdfunding, cattle fattening, agriculture, business strategy